How important are labor-market gender gaps in the South Caucasus? - Marc Teignier; David Cuberes (Economies, 2024)
In this paper, we use survey data from the South Caucasus countries (Armenia, Azerbaijan, and Georgia) to document the presence of gender gaps in the labor market and examine its consequences. To do the analysis, we use a numerical general-equilibrium occupational choice model with heterogeneous agents in entrepreneurial ability. We then introduce the observed gender gaps in labor-force participants, employers, and self-employed. We find that entrepreneurship gender gaps cause an average GDP loss of 6.2%, while gender gaps in labor-force participation cause an average GDP loss of 9%. Armenia (2007) displays the largest total loss and Georgia (2007, 2014) the smallest ones. We also decompose the gender gaps and their associated costs by households with different education levels and with and without dependents at home. Our results indicate that most of the income losses are driven by households with high education and those with dependents, especially those with both children and elderly at home.
Keywords: E02; J21; J24; O40; 330; gender inequality; entrepreneurship talent; factor allocation; aggregate productivity; span of control; South Caucasus; Armenia; Azerbaijan; Georgia